2007
DOI: 10.1262/jrd.19069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sperm Pretreatment on Efficiency of ICSI-Mediated Gene Transfer in Pigs

Abstract: Abstract. Intracytoplasmic sperm injection (ICSI)-mediated gene transfer has recently been shown to be an effective technique for producing transgenic pigs; however, the types of sperm pretreatment having the most beneficial effects on post-ICSI embryogenesis or transgenic efficiency have not been clarified. In the present study, we performed ICSI-mediated gene transfer using pig sperm subjected to various pretreatments and determined the developmental potential of sperm-injected oocytes and introduction effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…In mice and pigs, there has been no discussion regarding the state of the transgene after transgenic ICSI. In both species, it has been demonstrated that 5-25 transgene copies are integrated in one or two host genome loci [11,17]. Unfortunately, the size of transgene (5.5 kb) and amount of DNA in a blastocyst (<6 pg) make it very difficult to confirm transgene integration through techniques such as FISH or Southern blot in our experience.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…In mice and pigs, there has been no discussion regarding the state of the transgene after transgenic ICSI. In both species, it has been demonstrated that 5-25 transgene copies are integrated in one or two host genome loci [11,17]. Unfortunately, the size of transgene (5.5 kb) and amount of DNA in a blastocyst (<6 pg) make it very difficult to confirm transgene integration through techniques such as FISH or Southern blot in our experience.…”
mentioning
confidence: 88%
“…However, results obtained so far in mice and domestic animals have been inconsistent [10,[12][13][14][15][16]. On the other hand, ICSI has resulted in the production of transgenic offspring in murine and porcine species, while Southern Blot and FISH analyses in resultant embryos and offspring have proven efficient in demonstrating successful gene integration [11,17]. However, for successful large-scale application of transgenic ICSI to domestic species, it is critical to solve the ICSI fertilization problem associated with activation failure [18].…”
mentioning
confidence: 99%
“…In addition to PNI and SCNT, lentiviral transduction of zygotes 24,25 and intracytoplasmatic sperm injection (ICSI) 26,27 have been employed for transgenesis in the pig. Lentiviral transduction can produce high ratios of transgenic offspring (20-30 % transgenic offspring per treated embryos), but this technique frequently results in cell mosaicism and thus reduced germline transmission; the maximal cargo of foreign DNA with lentiviral vectors is about 7 kbp; and epigenetic silencing of the virally integrated constructs has been observed 13 .…”
Section: Germline Transgenesis In Pigsmentioning
confidence: 99%
“…Another limitation is that a laboratory with biosafety level 2 is required for lentivirus production and handling. ICSI of membrane-damaged (dead) spermatozoa incubated with foreign DNA has been used to produce transgenic piglets; however, this method is technically demanding and the reported success rates are low (<1 % transgenic offspring per treated oocytes) 26 .…”
Section: Germline Transgenesis In Pigsmentioning
confidence: 99%
“…A study showed that despite of obtaining high rates of morulae and blastocysts through IVF and LI, none of the embryos expressed the transgene (Perry et al,1999). On the other hand, various reports indicate that ICSI-mediated gene transfer is an effective and repeatable method to produce transgenic mice ( Perry et al, 1999) and pigs (Kurome et al, 2007). In 2011, by using ICSI, 91.6% GFP expressing embryos were obtained (Pereyra-Bonnet et al, 2011).…”
Section: Sperm-mediated Transgenesismentioning
confidence: 99%